2016
DOI: 10.1158/1541-7786.mcr-16-0018
|View full text |Cite
|
Sign up to set email alerts
|

PCBP1/HNRNP E1 Protects Chromosomal Integrity by Translational Regulation of CDC27

Abstract: Cdc27 is a core component of the anaphase-promoting complex/cyclosome (APC/C), a multi-subunit E3 ubiquitin ligase whose oscillatory activity is responsible for the metaphase-to-anaphase transition and mitotic exit. Here, in normal murine mammary gland epithelial cells (NMuMG), Cdc27 expression is controlled post-transcriptionally through the RNA binding protein heterogeneous nuclear ribonucleoprotein E1 (hnRNP E1/PCBP1). shRNA-mediated knockdown of hnRNP E1 abrogates translational silencing of the Cdc27 trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The function of the PCBP1 gene encoding the hnRNP E1 protein was first demonstrated through characterization of its role as a negative regulator of alternative splicing. Since then, many additional roles have also been discovered, and most of them appear to have critical participation in the maintenance of cell phenotype integrity [34,39,67] . At the molecular level, the ability of hnRNP E1 to specifically bind to mRNA species often leads to a direct or indirect regulation of their translation.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the PCBP1 gene encoding the hnRNP E1 protein was first demonstrated through characterization of its role as a negative regulator of alternative splicing. Since then, many additional roles have also been discovered, and most of them appear to have critical participation in the maintenance of cell phenotype integrity [34,39,67] . At the molecular level, the ability of hnRNP E1 to specifically bind to mRNA species often leads to a direct or indirect regulation of their translation.…”
Section: Resultsmentioning
confidence: 99%
“…Mub is a poly-C binding protein likely involved as an RNA-binding protein (Stoiber et al 2015) in posttranscriptional gene regulation, especially of splicing (Brooks et al 2015). One of its three polyC-binding, human orthologs, PCBP1, has been implicated in the translational regulation of cdc27 (Link et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…André et al [60] revealed that BARD1, the host gene of hsa_circRNA_102910, can be involved in lung epithelial cell damage and fibroblast proliferation in IPF. The target gene of hsa_circRNA_102100 and 102101 may be related to chromosomal aneuploidy integrity and flawed cell cycles in IPF [61]. Zinc finger MYM-type 2, the host gene of hsa_circRNA _101225, can be involved in IPF by binding to fibroblast growth factor receptor1 [62].…”
Section: The Role Of Circrna In the Development Of Ipfmentioning
confidence: 99%